Penerapan Algoritma Taboo Codes Untuk Mengkompresi File Audio - Zuraidah (Buletin Ilmiah Informatika Teknologi, 2022)
In today's increasingly rapid technological developments, many people use electronic devices such as mobile phones, computers, iPods or other electronic devices to listen to music. Music stored in storage media is in the form of audio files. Audio or sound has several different formats depending on the user's platform. An audio file format is a file format for storing digital audio data on a computer system. Which is usually in each format has a different size and very large. For that we need a technique that can change the size of a file to be smaller. This technique is called compression or better known as compression. In compressing audio files, the Taboo Codes algorithm is used. Where the principle of the Taboo Codes algorithm is to choose a positive integer parameter n and order a pattern of n bits to indicate the end of the code. So as a result we will be able to know how the procedures in compressing audio files. As well as the design of a software that can compress audio files by applying the Taboo Codes algorithm